Notes de recheche sur l'accentuation et le phrasé prosodique à la lumière des corpus de français - Avanzi, Mathieu (Travaux neuchâtelois de linguistique, 2013)
In this paper the main rules for stress assignment in French, the constraints relative to the formation of minor prosodic units (Accentual Phrases) and major prosodic units (Intonational Phrases, IP) are first recalled. A procedure developed in order to annotate semi-automatically these phenomena in different French corpora is then described. Finally the results of two studies are presented. The first one is conducted on a 4-hour long corpus (designed for the statistical study of regional variation in Swiss French). It aims at testing the robustness of two phonological rules implicated in the formation of Accentual Phrase in French (deaccentuation of pre-nominal adjectives (a sequel to the Align-XHead constraint), accentual clash avoidance rule). The second summarizes the main results obtained in the author’s PhD thesis (Avanzi, 2012). It is conducted on a set of data containing approximately 800 dislocated-sentences. It questions the weight of syntactic and information structure cues in front of prosodic structure cues in order to identify Intonational Phrase boundaries.